DYNAMIQUE DES RITES FUNERAIRES CHEZ LES TURUMBU DU TERRITOIRE D’ISANGI RESIDANT A KISANGANI, REPUBLIQUE DEMOCRATIQUE DU CONGO - Frédéric Esiso Asia Amani; Désiré Isetcha Tawiti; Itindi, Jérôme Waliala Apataki; Taylor Athongo Lilembu; Faustin Likaka Balombo; Christian Angbilia Mokalo; Alexis-Toussaint Kawaya Yuma (IJRDO - Journal of Social Science and Humanities Research, 2019)
The life of men in society is partly a function of the rites that accompany events according to circumstances. The funerary ritual as rite of passage constitutes a specific field of study of the anthropological works who are thus relatively documenting for multiple reasons for different social groups. This concern about funerary rites is spreading in Africa, especially at the level of socio-cultural transformations that would have affected them in terms of cultural mixing or acculturation. The dynamics of funerary rites among the Turumbu of the Territory of Isangi resident in Kisangani, Democratic Republic of Congo is the subject of this dissertation. This reflection will try to ascend to what level intervenes the change that these ritual activities undergo in the daily life of the Turumbu. The study will also analyzes the elements or factors behind these mutations or transformations and will summarize the writings on the death and origin of funerary rites and the future of the widow and children of the deceased. (his family) because we treat the funeral rites of the Turumbu man and not the woman. <br style="font-style: normal; font-variant: normal; font-weight: normal; letter-spacing: normal; line-height: normal; orphans: 2; text-align: -webkit-auto; text-indent: 0px; text-transform: none; white-space: normal; widows: 2; word-spacing: 0px; -webkit-text-size-adjust: auto; -webkit-text-stroke-width: 0px;"><br style="font-style: normal; font-variant: normal; font-weight: normal; letter-spacing: normal; line-height: normal; orphans: 2; text-align: -webkit-auto; text-indent: 0px; text-transform: none; white-space: normal; widows: 2; word-spacing: 0px; -webkit-text-size-adjust: auto; -webkit-text-stroke-width: 0px;">